Pathological features of primary sclerosing cholangitis identified by bile proteomic analysis - Rupp, Christian; Bode, Konrad A.; Leopold, Yvonne; Sauer, Peter; Gotthardt, Daniel (Biochimica et biophysica acta. Molecular basis of disease, 2018)
Primary sclerosing cholangitis (PSC) is a chronic cholestatic liver disease of unknown origin. Previous bile proteomic analyses in patients with PSC have revealed changes in disease activity specific to malignant transformation. In this study, we established a reference bile duct-derived bile proteome for PSC that can be used to evaluate biliary pathophysiology. Samples were collected from patients with PSC or with choledocholithiasis (control) (n=6 each). Furthermore, patients with PSC-associated cholangiocarcinoma (CC) and with CC without concomitant PSC were analyzed. None of the patients showed signs of inflammation or infection based on clinical and laboratory examinations. Proteins overexpressed in patients with PSC relative to control patients were detected by two-dimensional difference gel electrophoresis and identified by liquid chromatography-tandem mass spectrometry. Functional proteomic analysis was performed using STRING software. A total of 101 proteins were overexpressed in the bile fluid of patients with PSC but not in those of controls; the majority of these were predicted to be intracellular and related to the ribosomal and proteasomal pathways. On the other hand, 91 proteins were found only in the bile fluid of controls; most were derived from the extracellular space and were linked to cell adhesion, the complement system, and the coagulation cascade. In addition, proteins associated with inflammation and the innate immune response—e.g., cluster of differentiation 14, annexin-2, and components of the complement system—were upregulated in PSC. The most prominent pathways in PSC/CC-patients were inflammation associated cytokine and chemokine pathways, whereas in CC-patients the Wnt signaling pathway was upregulated. In PSC/CC-patients DIGE-analysis revealed biliary CD14 and Annexin-4 expression, among others, as the most prominent protein that discriminates between both cohorts. Thus, the bile-duct bile proteome of patients with PSC shows disease-specific changes associated with inflammation and the innate immune response even in the absence of obvious clinical signs of cholangitis, malignancy, or inflammation. This article is part of a Special Issue entitled: Cholangiocytes in Health and Diseaseedited by Jesus Banales, Marco Marzioni and Peter Jansen.